HUBUNGAN PEMAKAIAN OBAT-OBATAN DENGAN KEJADIAN MELASMA PADA PEKERJA WANITA PENYAPU JALAN - Ria " Sugiarti; Ari Pristiana Dewi; Fathra Annis Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract This study aims to determine the factors associated with the incidence of melasma in women worker street sweeper. This research is descriptive correlative with the technique of cross sectional study. Samples were taken using accidental sampling method that amount to 66 respondents. The analysis used is a univariate analysis with frequency distribution and bivariate with chi-square test. This study shows results that there is a relationship of drugs use with the incidence of melasma (p value = 0,005). The results of this study recommend the impotance of maintaining healthy skin and avoid prolonged sun exposure by using protective equipment such as large hats, masks and umbrellas and sunscreen. Keyword : relationship use of drugs, incidence of melasma,  women worker street sweeper